2013
DOI: 10.1371/journal.pone.0067573
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Spatial Scale Effect of Anthropogenic Factors on Species Distribution

Abstract: Patch context is a way to describe the effect that the surroundings exert on a landscape patch. Despite anthropogenic context alteration may affect species distributions by reducing the accessibility to suitable patches, species distribution modelling have rarely accounted for its effects explicitly. We propose a general framework to statistically detect the occurrence and the extent of such a factor, by combining presence-only data, spatial distribution models and information-theoretic model selection procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 60 publications
(100 reference statements)
0
18
0
Order By: Relevance
“…Even though no direct measures of habitat features that may potentially represent environmental stressors for the expression of head shape in lizards has been carried out to date, our data suggested that small island size, low habitat diversity, no human presence and therefore lack of human related habitats, drier and warmer climate regimes might promote reduced intensity of head's shape sexual dimorphism (Figs , ). This pattern is consistent with the hypothesis that unfavourable environmental conditions may actually represent a stress which limits the expression of SD, since common wall lizards are well known to be well adapted to human made habitats (such as buildings and drywalls or olive groves and vineyards) and are generally less thermophilus than other Italian lizards like, e.g., Podarcis siculus (Biaggini et al ., ; Mangiacotti et al ., ). Thus, the environmental conditions of small islets or islands kept at low habitat diversity may reliably impose more severe limits to lizard survival, and consequently to the allocation of resources in the expression of secondary sexual characters.…”
Section: Discussionmentioning
confidence: 99%
“…Even though no direct measures of habitat features that may potentially represent environmental stressors for the expression of head shape in lizards has been carried out to date, our data suggested that small island size, low habitat diversity, no human presence and therefore lack of human related habitats, drier and warmer climate regimes might promote reduced intensity of head's shape sexual dimorphism (Figs , ). This pattern is consistent with the hypothesis that unfavourable environmental conditions may actually represent a stress which limits the expression of SD, since common wall lizards are well known to be well adapted to human made habitats (such as buildings and drywalls or olive groves and vineyards) and are generally less thermophilus than other Italian lizards like, e.g., Podarcis siculus (Biaggini et al ., ; Mangiacotti et al ., ). Thus, the environmental conditions of small islets or islands kept at low habitat diversity may reliably impose more severe limits to lizard survival, and consequently to the allocation of resources in the expression of secondary sexual characters.…”
Section: Discussionmentioning
confidence: 99%
“…Variables related to landscape composition were calculated at different buffer-distances (hereafter, "scales") around each patch in each region. The different scales were selected based on reported dispersal distances for L. viridis [37][38][39]. Scales selected were: 50m, 150m, 250m,…”
Section: Calculating Patch Variables and Landscape Structuresmentioning
confidence: 99%
“…It is important to understand that the SDM outputs assume a species is present throughout all suitable habitats and overlaying them to estimate richness and composition is predisposed to include errors of commission and overestimate richness (Guisan & Rahbek, 2011;Pineda & Lobo, 2012). Species could be absent or uncommon at sites that are predicted to be environmentally suitable due to dispersal constraints, biotic interactions, unsuitable micro-habitats and stochastic effects (Heikkinen et al, 2006) or human habitat modification (Mangiacotti et al, 2013). For example, SDMs predicted 26 species could occur at Middle Creek in Victoria where Hawking and New (2002) sampled odonates (larvae and adults) intensively on 20 visits over three years.…”
Section: Richnessmentioning
confidence: 99%